Marketing the products of aquaculture - Shaw, Susan A. (Food and Agriculture Organization of the United Nations, 1986)
This book describes how the concepts and practice of modern marketing management can be applied in the fisheries and aquaculture industry. It explains how an improvement inn business management, especially in marketing can increase both sales and profits. The early chapters focus on the concept of satisfying customer need and the use of market research to construct marketing system models which can be used to correctly position existing products and formulate plans for new products or strategies. Then it is shown that execution of marketing programmes involves the other variables of price, promotion and distribution. Application and control of these variables is described with examples from various sectors of the industry. The text assumes no previous knowledge of marketing, being designed for use by practising managers in the commercial and public sectors and to provide an introductory text for courses on businees management in fisheries and aquaculture.